The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0103-51502013000300006
|View full text |Cite
|
Sign up to set email alerts
|

Análise de parâmetros funcionais pulmonares e da qualidade de vida na revascularização do miocárdio

Abstract: Fisioter Mov. 2013 jul/set;26(3):525-36 ISSN 0103-5150 Fisioter. Mov., Curitiba, v. 26, n. 3, p. 525-536, jul./set. 2013 Licenciado sob uma Licença Creative Commons doi: [T] Análise de parâmetros funcionais pulmonares e da qualidade de vida na revascularização do miocárdio [I] Analysis of pulmonary functional parameters and health-related quality of life in patients submitted to coronary arterial bypass graft [A] Raquel Annoni [a] , Wilton Rodrigues Silva [b] , Resumo Introdução: A cirurgia de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
5
0
4
Order By: Relevance
“…On the other hand, Annoni et al 17 observed a significant increase in MEP and PEF, which may have been correlated with the small sample size, and collaboration and learning of patients to perform the tests, since they were evaluated daily from the first postoperative period until the day of discharge.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Annoni et al 17 observed a significant increase in MEP and PEF, which may have been correlated with the small sample size, and collaboration and learning of patients to perform the tests, since they were evaluated daily from the first postoperative period until the day of discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the occurrence of ARDS and sepsis in puerperal women with HELLP syndrome can be associated, which can lead to the worsening of this pathology, making intensive care necessary 4,13 . * Reference values predicted in literature 9,14 In this context, sepsis can manifest itself with signs such as acute pulmonary edema of non-cardiac origin, after hypoxemia; not infrequently, acute lung injury or ARDS is diagnosed. In most of these cases, there is a need for invasive mechanical ventilation (IMV), a protective strategy for the lung, using ventilatory parameters such as driving pressure, which directly interferes with Cst and regional pulmonary ventilation 8,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor evaluated by EIT is static lung compliance (Cst), facilitating the identification of alveolar collapses, when present, in some regions of the lung (decreased Cst), as well as reduced alveolar hyperdistension in other regions (causing increased Cst), during, for example, decremental titration of positive end-expiratory pressure (PEEP) in patients with ARDS 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The 6MWT is a submaximal test that allows the assessment of the respiratory, cardiac and metabolic tracts, that is widely applied in physical rehabilitation programs and in treatment of patients with cardiopulmonary diseases. [9][10][11][12][13][14] In patients with CF, muscle weakness and functional impairment associated with malnutrition are factors that limit physical capacity. [15][16][17]…”
Section: Introductionmentioning
confidence: 99%